An Investigation of Various Perspectives of Cultures and Societies of the Indus Civilization: Unraveling the Trade Networks and Cultural Dynamics of the Indus Civilization (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The accompanying paper will concentrate on some of the major new points of view on the Indus Civilization that are the outcome of new revelations at destinations in both the center districts of the Indus Civilization that are found in Pakistan and India. New research in adjoining locales are additionally uncovering proof of ancient communications between the Indus district and the domains of modern Afghanistan, Turkmenistan, Iran, Oman, the United Arab Emirates, Bahrain, Kuwait, Iraq, Syria, and significantly assist away from home. A couple of these critical revelations will be examined to highlight the difficulties that we confront in understanding the intricate systems of exchange and communication that were available in the 3,d thousand years BCE.